Effect of γ-Tocotrienol and α-Tocopherol on blood glutathione and tumor marker enzymes during chemical hepatocarcinogenesis in the rat - Rahmat, Asmah; Wan Ngah, Wan Zurinah; Jarien, Zanariah; Ismail, Rosnani; Marzuki, Alini; Abdul Kadir, Khalid; Shamaan, Nor Aripin (The Society for Free Radical Research Japan, 1993)
The protective effect of two types of vitamin E (α-tocopherol and γ-tocotrienol) in rats treated with diethylnitrosamine (DEN) and 2-acetylaminofluorene (AAF) were studied by determination of plasma alkaline phosphatase (ALP), plasma and liver microsomal y-glutamyl transpeptidase (GGT) activities, and blood glutathione (GSH). Rats treated with DEN/AAF had significantly elevated plasma and microsomal GGT, plasma ALP activities, and blood GSH levels compared with the normal controls (Ρ<0.05). Supplementation with vitamin E of normal controls did not affect the enzyme activities or blood GSH. in rats treated with DEN/AAF, vitamin E supplementation attenuated GGT and ALP activitiesand blood GSH levels. the optimum dose required for highest attenuation of the tumor marker enzyme activities was 34 mg/kg diet for α-tocopherol and 30 mg/kg diet for y-tocotrienol. Higher doses of the vitamin did not show further attenuation in the level of the tumor marker enzyme activities.